Electrogenerated Fe(I) Porphyrins: Efficient Electrocatalysts for Reductive Dechlorination of DDT in N, N′‐Dimethylformamide. Issue 6 (9th May 2013) - Zhang, Ying; Shen, Wei; Ou, Zhongping; Zhu, Weihua; Fang, Yuangyuan; Kadish, Karl M.
Abstract Two iron(I) porphyrins were electrogenerated and then utilized as catalysts for the reductive dechlorination of 1, 1‐bis(4‐chlorophenyl)‐2, 2, 2‐trichloroethane (DDT) in N, N′‐dimethylformamide. No reaction is observed between DDT and the Fe(III) or Fe(II) forms of the porphyrin, but the electrogenerated Fe(I) porphyrin efficiently catalyzes the electroreduction of DDT to give (1, 1‐bis(4‐chlorophenyl)‐2, 2‐dichloroethane) DDD, (1, 1‐bis(4‐chlorophenyl)‐2, 2‐dichloroethylene) DDE and (1, 1‐bis(4‐chlorophenyl)‐2‐dichloroethane) DDMU as determined by GC‐MS analysis. The reductive dechlorination was monitored by electrochemistry, controlled potential electrolysis and spectroelectrochemistry and a mechanism for the reaction involving the reduced porphyrins and DDT is proposed. Comparisons are also made between the catalytic properties of metalloporphyrins containing iron, cobalt and manganese central metal ions under the same solution conditions.